2012
DOI: 10.1037/a0026984
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility to early literacy intervention in children with mild perinatal adversities: Short- and long-term effects of a randomized control trial.

Abstract: In a randomized control trial, the authors tested whether short-and long-term effects of an early literacy intervention are moderated by mild perinatal adversities in accordance with differential susceptibility theory. One-hundred 5-year-old children (58% male) who scored at or below the 30th percentile on early literacy measures were randomized to a Web-based remedial early literacy program Living Letters or a treated control group. Parents gave written informed consent to access the perinatal data of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 70 publications
3
57
1
Order By: Relevance
“…For example, cognitive development of mild small for gestational age children is delayed, with increased risk of learning disabilities in childhood, and lower educational achievement among adults born near-term (Johnson & Breslau, 2000;Kirkegaard et al, 2006;Nomura et al, 2009;Van der Kooy-Hofland et al, 2012). We argue here that mild perinatal adversities not only are a risk for the children involved but also an asset as it makes them benefit more from benign environments compared to their peers born at term Van der Kooy-Hofland et al, 2012). …”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…For example, cognitive development of mild small for gestational age children is delayed, with increased risk of learning disabilities in childhood, and lower educational achievement among adults born near-term (Johnson & Breslau, 2000;Kirkegaard et al, 2006;Nomura et al, 2009;Van der Kooy-Hofland et al, 2012). We argue here that mild perinatal adversities not only are a risk for the children involved but also an asset as it makes them benefit more from benign environments compared to their peers born at term Van der Kooy-Hofland et al, 2012). …”
Section: Introductionmentioning
confidence: 75%
“…However, children differ in their susceptibility to the effects of parental care and other environmental influences due to genetic, behavioral, or physiological susceptibility factors (Ellis, Boyce, Belsky, Bakermans-Kranenburg, & Van IJzendoorn, 2011). Previous research has shown that children with a history of mild perinatal adversities (late prematurity or low birth weight at full term birth) are more susceptible to environmental influences than children without perinatal adversities (Van der Kooy-Hofland, Van der Kooy, Bus, Van IJzendoorn, & Bonsel, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent series of adolescent reading interventions summarized in Vaughn and Fletcher (2012), one year of intervention produced small effects that largely were not statistically significant in a much larger sample. However, continuing the intervention with adolescents who had not responded adequately for two to three years led to moderate effect size advantages after the second year and a large effect on reading comprehension after three years, the latter partly because the standard scores for the comparison group declined from Grades 6 to 8.…”
Section: Discussionmentioning
confidence: 97%